Zakat is not Just Charity Why Professional Fund Management Shapes the Future of the Ummah - Furkony, Deni Konkon Furkony; Ridwan, Ahmad Hasan; Mahmud, Mahmud; Suntana, Ija; Syaripudin, Enceng Iip; Mohd, Ismail Bin (Involvement International Journal of Business, 2025)
Zakat, often perceived merely as a religious obligation or charitable act, holds untapped potential as a strategic instrument for socio-economic transformation in Muslim communities. This study argues that zakat must be viewed not just as an act of giving, but as a fund requiring professional management to realize its full impact on community development and the future of the Ummah. Using a qualitative research design, the study explores professional fund management practices in selected Zakat Management Units (UPZs) across Indonesia. Data were collected through in-depth interviews with UPZ leaders and financial managers, as well as document analysis of financial reports, program structures, and governance models. The findings indicate that UPZs which adopt professional financial governance—characterized by transparency, accountability, data-driven planning, and skilled human resources—are significantly more effective in achieving measurable outcomes such as improved mustahik welfare, sustainable livelihoods, and increased trust from muzakki. Professionalism transforms zakat from reactive charity into proactive socio-economic empowerment. This study underscores the urgency of redefining zakat management frameworks to embrace modern financial and organizational practices while remaining rooted in Sharia principles. As zakat institutions become more professional, they not only fulfill their spiritual mandate but also emerge as pivotal players in driving the long-term resilience and welfare of the Ummah. The future of Islamic social finance lies in bridging tradition with innovation through professional stewardship.